Vitamin D protection from rat diabetic nephropathy is partly mediated through Klotho expression and renin–angiotensin inhibition. (20th October 2018) - Eltablawy, Nashwa; Ashour, Hend; Rashed, Laila Ahmed; Hamza, Wael Mostafa
Abstract: Objective: We hypothesised that vitamin D has a beneficial renal protective effect from diabetic nephropathy (DN). Methods: Four rat groups were included: normal control (control), type 2 diabetes for eight weeks (DM), treated group with angiotensin receptor blocker losartan (DM + L), and vitamin D-treated group started from the onset of diabetes (DM + Vit D). Results: In the both treated groups, we found a significant ( p  < .05) reduction in the renal pro-inflammatory and profibrotic markers induced by diabetes. Vitamin D caused more reduction in monocyte chemoattractant protein-1 (MCP-1), transforming growth factor (TGFβ-1), and renin–angiotensin levels that gave better kidney function compared to the DM + L group. Conclusion: Vitamin D may have a valuable role in the renal protective effect from DN, this may occur via expression of its VDR, Klotho and blocking renin–angiotensin activation, so vitamin D should be considered as a target in renal prophylactic measures against DN.